Benefit of Belatacept in Cord Blood-Derived Regulatory T Cell-Mediated Suppression of Alloimmune Response. (27th September 2021) - He, Xing; Li, Sang; Zhang, Juan; Cao, Lu; Yang, Cejun; Rong, Pengfei; Yi, Shounan; Ghimire, Kedar; Ma, Xiaoqian; Wang, Wei
The role of Regulatory T cells (Tregs) in tolerance induction post-transplantation is well-established, but Tregs adoptive transfer alone without combined immunosuppressants have failed so far in achieving clinical outcomes. Here we applied a set of well-designed criteria to test the influence of commonly used immunosuppressants (belatacept, tacrolimus, and mycophenolate) on cord blood-derived Tregs (CB-Tregs). Our study shows that while none of these immunosuppressants modulated the stability and expression of homing molecules by CB-Tregs, belatacept met all other selective criteria, shown by its ability to enhance CB-Tregs-mediated in vitro suppression of the allogeneic response without affecting their viability, proliferation, mitochondrial metabolism and expression of functional markers. In contrast, treatment with tacrolimus or mycophenolate led to reduced expression of functional molecule GITR in CB-Tregs, impaired their viability, proliferation and mitochondrial metabolism. These findings indicate that belatacept could be considered as a candidate in Tregs-based clinical immunomodulation regimens to induce transplant tolerance.